1994
DOI: 10.1046/j.1365-313x.1994.6040537.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a β‐type proteasome subunit from Arabidopsis thaliana co‐expressed at a high level with an α‐type proteasome subunit early in the cell cycle

Abstract: Proteasomes are the essential components of complexes involved in an extralysosomal energy- and ubiquitin-dependent proteolytic pathway. The first alpha-type proteasome subunit in plants has recently been described. In this work, the sequence of the first beta-type proteasome subunit in plants, isolated from Arabidopsis thaliana cDNA libraries is reported. The mRNA accumulation of both subunits was analysed and compared with those of the ubiquitin and histone mRNAs, in different tissues and during re-initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…All known 20S proteasome subunits contain conserved sequence motifs (Genschik et al, 1992(Genschik et al, , 1994Lupas et al, 1994) that are not found in the 21D7 polypeptide. Moreover, the animal homolog of the 21D7 protein was isolated from bovine cells as a subunit of the PA700 regulatory complex of the 26S proteasome (DeMartino et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All known 20S proteasome subunits contain conserved sequence motifs (Genschik et al, 1992(Genschik et al, , 1994Lupas et al, 1994) that are not found in the 21D7 polypeptide. Moreover, the animal homolog of the 21D7 protein was isolated from bovine cells as a subunit of the PA700 regulatory complex of the 26S proteasome (DeMartino et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis genes encoding a and P subunits of plant 20s proteasomes have been isolated (Genschik et al, 1992(Genschik et al, , 1994). In addition, several genes encoding putative subunits of the 26s proteasome have been cloned recently: an Arabidopsis gene for a protein with the ubiquitin binding site (Vannocker et al, 1996) and two ATPase genes (Suzuka et al, 1994;Prombona et al, 1995).…”
mentioning
confidence: 99%
“…Nevertheless, this point, as well as the change in mRNA level of the other 20S proteasome subunits during carbon starvation, will have to be checked when the sequences of the corresponding genes become available. To date, because in most animal, yeast, and plant materials studied so far the expression of the various proteasome subunits seems to occurs via a concerted mechanism (Genschik et al, 1994;Ichihara and Tanaka, 1995;Fu et al, 1998), it may be reasonably assumed that the expression of the other subunits of maize 20S proteasome were similarly decreased. This suggests that, in carbon-starved maize root tips, 20S proteasome expression was modified presumably through: (a) a decrease in proteasome gene transcription, and (b) an increase in proteasome stability and/or in mRNA translation efficiency.…”
Section: Modifications Of 20s Proteasome In Carbon-starved Tissuesmentioning
confidence: 99%
“…Genes for two a-like and one p-like subunit have been cloned from Arabidopsis (Genschik et al, 1992b(Genschik et al, , 1994Shirley and Goodman, 1993). DNA sequence encoding one of the a-like subunits is contained within a region of the genome that can be deleted without apparent phenotypic consequences (Shirley and Goodman, 1993).…”
Section: Proteinases In Plant Cellsmentioning
confidence: 99%